Application of Coconut Shell Liquid Smoke to Control Fusarium Wilt Disease on Hevea brasiliensis Muell. Arg. - Wahyu Ristiani; Ratna Yuniati; Retno Lestari; Wisnu Wardhana (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The study aims to observe coconut shell liquid smoke as a bio-fungicide in controlling F. oxysporum growth. The treatment was applied on sample i.e., coconut shield liquid smoke as a bio-fungicide, compared with a chemical fungicide as a positive control, and without treatment as a negative control. The direct observation was conducted for four weeks, with treatment application every seven days. The analysis of variance test shows the difference of three treatments in controlling the F. oxysporum growth for each observation period. Still, it has no difference in average in fungal growth after treatment. According to the results of weekly observations, coconut shell liquid smoke biofungicide reduces the disease severity on the tapping fields infected by F. oxysporum in the range of 13-21%, whereas chemical fungicide reduces the disease severity in the range of 1-10%. In conclusion, the ability of coconut shell liquid smoke bio-fungicide to control is relatively shorter compared to chemical fungicide. Based on the inhibition ability of coconut shield liquid smoke, it is recommended that utilize various grades of coconut shell liquid smoke as a comparison.